2017
DOI: 10.1002/pd.5138
|View full text |Cite
|
Sign up to set email alerts
|

Implications of fetoplacental mosaicism on cell‐free DNA testing for sex chromosome aneuploidies

Abstract: Mosaicism is a major issue for SCA cfDNA testing, and prenatal confirmation, preferentially with amniocentesis if there are no ultrasound anomalies, remains important in counseling. As PPV varies on the basis of the presence of an ultrasound anomaly, skilled evaluation is critical. © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 21 publications
7
57
0
Order By: Relevance
“…The use of genome‐wide cfDNA panels impacts the usually extremely low false positive rate of the test, due to cases of confined placental mosaicism (CPM) . CPM is especially common in sex chromosomes, particularly monosomy X, and rare autosomal trisomies such as trisomy 7, 16, 8 and 20. This also negatively affects the positive predictive value of the screening test, which inevitably decreases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of genome‐wide cfDNA panels impacts the usually extremely low false positive rate of the test, due to cases of confined placental mosaicism (CPM) . CPM is especially common in sex chromosomes, particularly monosomy X, and rare autosomal trisomies such as trisomy 7, 16, 8 and 20. This also negatively affects the positive predictive value of the screening test, which inevitably decreases .…”
Section: Discussionmentioning
confidence: 99%
“…CPM is especially common in sex chromosomes, particularly monosomy X, and rare autosomal trisomies such as trisomy 7, 16, 8 and 20. This also negatively affects the positive predictive value of the screening test, which inevitably decreases . The net result is that genome‐wide cfDNA undermines the main advantage of this screening test above the CT, which is to reduce the need for invasive testing.…”
Section: Discussionmentioning
confidence: 99%
“…This relates primarily to fetuses with monosomy 45, X with normal ultrasound findings. The positive predictive value of an abnormal cfDNA analysis is therefore only approximately 53 % in this group, while the PPV would be 98.8 % in the case of an abnormal ultrasound finding such as fetal nuchal edema or hygroma [134]. Both in the case of a normal finding regarding fetal sex after cfDNA and in a pathological finding, sonographic verification of the fetal sex organs should be performed to rule out developmental disorders [135].…”
Section: Sex Chromosome Aneuploidies Early Detection Of Fetal Sexmentioning
confidence: 88%
“…However, if NIPT reveals abnormality, invasive prenatal test like amniocentesis is required for definitive diagnosis. And it is important to note that confined placental mosaic or vanishing twin can yield misleading results [18,19]. Sekizawa et al reported high accuracy of fetal gender determination using cfDNA since seven weeks of gestation [20].…”
Section: Discussionmentioning
confidence: 99%